The Support Needs of Patients Requesting Medical Aid in Dying and Their Relatives: A Qualitative Study Using Semi-Structured Interviews and Written Narratives - Stijn Vissers; Stijn Vissers; Joni Gilissen; Joni Gilissen; Joachim Cohen; Joachim Cohen; Luc Deliens; Luc Deliens; Freddy Mortier; Freddy Mortier; Freddy Mortier; Kenneth Chambaere; et al. (International Journal of Public Health, 2024)
ObjectivesTo explore the support needs that patients and relatives experience throughout their medical aid in dying (MAID) trajectories.MethodsA qualitative study in Belgium in 2022 using 1) semi-structured interviews with and personal written narratives of patients requesting MAID and 2) semi-structured interviews with relatives of patients requesting MAID. We performed a qualitative content analysis.ResultsWe included in our analysis the lived experiences of 15 patients and 21 of their relatives. We identified eight types of support needs: support for 1) maximizing daily functioning (only reported by patients), 2) making sense of the unbearable suffering (only reported by relatives), 3) managing meaningful activities, 4) navigating existential questions, 5) psycho-emotional regulation, 6) facilitating social interaction, 7) understanding the process toward MAID, 8) and handling organizational and practical matters.ConclusionPatients and relatives might experience multidimensional support needs throughout their MAID trajectories. Our findings suggest that they experience these trajectories more as social/existential pathways than as medical ones. A palliative care approach may be an effective way to fulfill the support needs of patients and relatives throughout their MAID trajectories.